Maximizing Village Potential through the Creation of Dish Soap Products from Orange Peels in Umbulrejo Village by KKN Kolaboratif 105: Pemaksimalan Potensi Desa Melalui Pembuatan Produk Sabun Cuci Piring dari Kulit Jeruk di Desa Umbulrejo oleh KKN Kolaboratif 105 - Lumbantoruan, Sehat Binsar Pardomuan; Dwi Amelia, Reza; Dika Maharani, Elshinta; Firgina Rahman, Farah; Sa’adiyah, Fatimatus; Nurmahadi, Brian; Putri Oktafiana, Sindi; Pradiana, Yulia; Kharisma Rindiantika, Bella; Zahra Anggraini, Widaddhiya; Mukarromah, Ma’isyatul; Vebriana Natalia, Vina; Suryaningrum, Yuli (KHD Production, 2023)
Umbulrejo Village is one of the villages in Jember Regency that holds potential in the form of fruit farming. Every year, Umbulrejo Village becomes one of the orange-producing villages whose products are sold even beyond the island. Until now, orange commodities have only been utilized as fresh agricultural products sold by the local community. Therefore, there is a need for innovative orange processing to manage the available orange resources. Efforts to empower the community to independently utilize their local potential include providing knowledge and skills related to the entrepreneurial process of making handmade dish soap. The aim of this activity is to maximize the village's potential in processing orange peels into dish soap products, while also creating new business opportunities to enhance the local economy. The implementation of the activity includes initial socialization, training in dish soap production, and packaging. The results of the activity indicate that it can (1) provide an understanding of how to make dish soap along with the materials and tools used, (2) introduce the community to the opportunity of a home-based dish soap business. The production of dish soap using orange peels as a primary ingredient still needs further development to enable mass production and acceptance by the wider community. Additionally, government support is required for obtaining circulation permits and product viability.